Optimasi sifat organoleptik, indeks, dan beban glikemik formula enteral berbasis tepung tempe dan tepung bengkuang - Ayu Rahadiyanti; Choirun Nissa; Wahyu Ilmi Annisa; Lilis Wijayanti; Fillah Fithra Dieny; Deny Yudi Fitranti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
Optimization of organoleptic, glycemic index, and a load of enteral formula based on tempe and jicama flourBackground: Tempeh and jicama have the potential effect as hypoglycemic agents. Hyperglycemic patients are recommended to consume formula with a low glycemic index to control blood glucose levels properly. Although balancing and roasting could improve the aromas of tempeh flour, research is lacking on tempeh powder-based enteral formula.Objective: This study aimed to analyze the organoleptic, glycemic index, and glycemic load of enteral formulas based on tempeh and jicama flour to meet the requirements of enteral formulas for hyperglycemic patients.Methods: Experimental research with 3 levels of treatment, namely variations in the ratio of tempeh flour and jicama flour with formulas 1 (1:1); 2 (3:2); and 3 (4:7) with two methods, namely steam blanching and roasting before tempeh drying. An organoleptic test using a hedonic test was carried out on 25 semi-trained panelists. One-shot case study glycemic index and glycemic load test on 30 subjects met the inclusion criteria. Data analysis used the Kruskal-Wallis test.Results: The color, aroma, and taste in formula 3 were acceptable to the panelists, but the texture was less favorable. Formula 3 has a glycemic index of 55.20 and a glycemic load of 14.90. There was no difference in an index and glycemic load in the 3 enteral formulas.Conclusion: Formula 3, with a ratio of 4:7, a moderate glycemic index, and load, could be acceptable to the panelists.